Attitudes of Geography Teachers towards the Use of the Blended Learning Strategy and its Relationship to The Degree of Employment from their Point of View - Alshamout, Mathayel Fayyad Hayyyan (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the attitudes of Geography teachers towards the use of the blended learning strategy and its relationship to the degree of employment from their point of view. The study used the descriptive related approach, two questionnaires were development first one to determine the attitudes of Geography teachers towards the use of the blended learning strategy, the second to determine the level of employment this strategy, the sample of study consisted from (43) female and male teacher. However, the finding of study showed that the attitudes of Geography teachers towards the use of the blended learning strategy were positive with average (3.86 out of 5), and the level of implementation was moderated with average (3.66 out of 5). The finding also showed there weren’t any significant difference in the degree of using blended learning strategy refers to variable of teacher's sex. Furthermore, there were significant differences at (α ≤ 0.05) according to teacher qualification for higher education.
Keywords: Attitudes; Blended Learning; Geography Teachers